2004
DOI: 10.1007/s00024-004-2526-1
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Technique for Simulating Wide-band Strong Ground Motion for Two Recent Himalayan Earthquakes

Abstract: A simplified technique for simulation of wide-band strong motion based on simple regression relations and Empirical Green's Function (EGF) technique by IRIKURA (1986) is presented in this paper. The method uses the acceleration envelope as a shaping window for a filtered white Gaussian noise, to get the synthetic accelerogram from each subfault. Correction factors for slip of large and small events and transmission factors at each boundary of different layers are included in this synthetic accelerogram. The sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…The most sought after information for generating synthetic ground-motion data consists of region-specific input parameters such as stress drop, quality factor, geometrical spreading, and site geology. Recently, a few researchers have investigated these parameters for the Garhwal region (Joshi 2004(Joshi , 2006Kumar et al 2005;Singh et al 2004;Yu et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The most sought after information for generating synthetic ground-motion data consists of region-specific input parameters such as stress drop, quality factor, geometrical spreading, and site geology. Recently, a few researchers have investigated these parameters for the Garhwal region (Joshi 2004(Joshi , 2006Kumar et al 2005;Singh et al 2004;Yu et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The models obtained using this relationship has been tested by Joshi (2004) for its application for the Himalayan region. In this study, the rupture plane along the identified lineament is considered as rectangular in shape (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Before using these regression relations, their applicability needs to be checked. This was done in the previous study by Joshi (2004) for Uttarkashi and Chamoli earthquakes. The minimum root mean square error (RMSE) was found in the case of the ground motion model by Abrahamson and Litehiser (1989).…”
Section: Scaling Laws For the Study Regionmentioning
confidence: 99%
See 2 more Smart Citations